Engaging Feminist Histories / Hemmings, Clare. 2011. Why Stories Matter: The Political Grammar of Feminist Theory. Durham, NC: Duke UP / Hesford, Victoria. 2013. Feeling Women’s Liberation. Durham, NC: Duke UP / Scott, Joan Wallach. 2011. The Fantasy of Feminist History. Durham, NC: Duke UP - Groeneveld, Elizabeth (Atlantis)

(untitled) (Mount Saint Vincent University, 2014)
This review essay considers three recently published texts that centrally engage with the question of how one writes about feminisms and feminist histories in ways that do justice to their complexity and dynamism.